Forensic Analysis Reveals Acute Decompensation of Chronic Heart Failure in a 3500‐Year‐Old Egyptian Dignitary. Issue 5 (30th June 2016) - Bianucci, Raffaella; Loynes, Robert D.; Sutherland, M. Linda; Lallo, Rudy; Kay, Gemma L.; Froesch, Philippe; Pallen, Mark J.; Charlier, Philippe; Nerlich, Andreas G.
Abstract: Naturally preserved and embalmed bodies from archeological contexts represent a powerful source of information for forensic investigators. They allow one to ascertain pathology, cause of death, to enhance diagnostic methodology, and to improve the analysis of altered remains. We investigated the complete head and lung remnants of a 3, 500‐year‐old Egyptian dignitary by radiological, microscopic, and genetic approaches. The individual, a middle‐aged male, suffered from severe periodontitis, mild atherosclerosis, and experienced cardiogenic pulmonary insufficiency with recurrent mini‐bleeds and pulmonary edema. Histology and ancient DNA analyses excluded the presence of Mycobacterium tuberculosis or of any other pathogenic species. Based on our collection of evidence, we propose that acute decompensation complicating chronic cardiac insufficiency was the likely cause of death. The underlying causes for this failure remain unknown although chronic hypertension appears to be the most likely candidate. Our finding represents the earliest reported case of chronic heart failure in ancient mummies.